(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Muhammad Nasir al-Din al-Albani is one of the few prominent scholars of hadith in the 20th century. Al-Albani produced many works in various disciplines based on research of thousands of hadith manuscripts. Thus al-Albani’s thought in the field of da’wah or preaching to Islam is greatly influenced by the discipline of hadith studies. His painstaking study of prophetic hadith had formed his stream of thought towards the scientific approach, without fanaticism to any party. Hence this article attempts to highlight the methodology, principle and implications of al-Albani’s da’wah based on his academic works, while correcting perception towards them. Facts presented were obtained from al-Albani original as well as translated writings. Al-Albani is deeply inclined towards the Salafi da’wah methodology as advocated by various predecessors. Through this methodology, al-Albani successfully manage to revive Muslim’s awareness of the importance of returning to the guidance of both the Qur’an and the Sunnah based on the understanding of the Salaf, while combating innovations in religion which undermine their progress. Striving also to focus al-Albani’s contributions in da’wah, this article hopes to enhance a more harmonious relationship between the Muslim community and the institution of Islamic scholars.